In vitro and in vivo brain ablation created by high-intensity focused ultrasound and monitored by MRI - Ioannides, Kleanthis; Mylonas, Nicos; Hadjisavvas, Venos; Iosif, Demitris; Damianou, Christakis A.; Couppis, Andreas (My University, 2009)
In this paper, magnetic resonance imaging (MRI) is investigated for monitoring small and large lesions created by high-intensity focused ultrasound (HIFU) in freshly excised lamb brain and in rabbit brain in vivo. A single-element spherically focused transducer of 5 cm diameter, focusing at 10 cm and operating at 1 MHz was used. A prototype MRI-compatible positioning device that is used to navigate the transducer is described. The effects of HIFU were investigated using T1-W and T2-W fast spin echo (FSE) and fluid-attenuated inversion recovery (FLAIR). T2-W FSE and FLAIR show better anatomical details within the brain than T1-W FSE, but with T1-W FSE, the contrast between lesion and brain is higher for both thermal and bubbly lesions. The best contrast between lesion and brain with T1-W FSE is obtained with TR above 500 ms, whereas with T2-W FSE, the best contrast is observed between 40 and 60 ms. The maximum contrast to noise ratio (CNR) measured with T1-W FSE was approximately 20. With T2-W FSE, the corresponding CNR was approximately 12. With this system, we were able to create large lesions (by producing overlapping lesions), and it was possible to monitor these lesions with MRI with excellent contrast. The length of the lesions in vivo brain was much higher than the length in vitro, indicating that the penetration in the in vitro brain is limited, possibly by reflection due to trapped bubbles in the blood vessels. This paper demonstrates that HIFU has the potential to treat brain tumors in humans. This could be done either using a single-element transducer with a frequency around 1 MHZ or using a multi-element transducer. © 2006 IEEE.
Keywords: In vitro; In vivo; Ultrasonic imaging; Monitoring; Magnetic resonance imaging; Lesions; Focusing; Ultrasonic transducers; Rabbits; Prototypes